2014
DOI: 10.1172/jci77198
|View full text |Cite
|
Sign up to set email alerts
|

Too much of a good thing: immunodeficiency due to hyperactive PI3K signaling

Abstract: C o m m e n t a r y 3 6 8 8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…The phenotype of activated PI3K-d syndrome (APDS) includes recurrent respiratory infections, severe viral infections, autoimmunity, lymphoproliferation/lymphoma and neurodevelopmental problems, accompanied by variable lymphopenia with increased circulating transitional B lymphocytes, increased IgM and impaired vaccine responses, and reduced naive and increased senescent T lymphocytes with reduced proliferative capacity. [1][2][3] Although variable in severity, it can present as or evolve into a profound combined immunodeficiency, justifying the consideration of hematopoetic stem cell transplantation (HSCT). We report the first series of HSCT in this disorder.…”
Section: Hematopoietic Stem Cell Transplant In Patients With Activatementioning
confidence: 99%
See 1 more Smart Citation
“…The phenotype of activated PI3K-d syndrome (APDS) includes recurrent respiratory infections, severe viral infections, autoimmunity, lymphoproliferation/lymphoma and neurodevelopmental problems, accompanied by variable lymphopenia with increased circulating transitional B lymphocytes, increased IgM and impaired vaccine responses, and reduced naive and increased senescent T lymphocytes with reduced proliferative capacity. [1][2][3] Although variable in severity, it can present as or evolve into a profound combined immunodeficiency, justifying the consideration of hematopoetic stem cell transplantation (HSCT). We report the first series of HSCT in this disorder.…”
Section: Hematopoietic Stem Cell Transplant In Patients With Activatementioning
confidence: 99%
“…Lucas et al 4 Patients with APDS may benefit from rapamycin or other inhibitors of PI3K. 1,2,5 Despite reports of impressive responses, not all patients achieve durable disease remission. Chronic morbidity and death from severe infection and lymphoma are reported such that HSCT is a relevant consideration.…”
Section: Hematopoietic Stem Cell Transplant In Patients With Activatementioning
confidence: 99%
“…Recently, 2 important articles approached the role of thymic B cells in murine models, using transfer experiments and deficient lines (eg, autoimmune regulator [Aire] knock-out animals). They demonstrated that murine thymic B cells are potent APCs to autoreactive T cells 2 and that they can harbor different self tissue-restricted antigens (TRAs) induced by Aire expression. 3 But only little is known about the fate and function of human B cells in thymus with mostly immunochemistry data.…”
Section: B Cells Differentiate In Human Thymus and Express Airementioning
confidence: 99%
“…Higher steady-state levels of p-AKT are observed in vitro and ex vivo , indicating that the mutations are GOF. Thus, GOF mutations of PIK3R1 and PIK3CD seem to underlie immunological and clinical phenocopies [160,161]. PIK3R1 is more broadly expressed than PIK3CD.…”
Section: Infection With or Without Autoimmunity And Without Autoinflamentioning
confidence: 99%